Hate Speech dalam Masyarakat Post Truth - Wiji Nurasih (MAGHZA, 2019)
Hate speech is increasingly becoming a serious threat to the unity of the Republic of Indonesia which is very diverse. The characteristics of people in the post-truth era that are more influenced by personal opinion than reality cause their emotions and sentiments to be easily ignited which results in intolerance and strife. How bad is the Qur'an which in some verses forbids the utterance of hate speech, one of which is through verse 1 of Surah al-Humazah, which strongly denounces and cursing. This study aims to analyze the behavior of hate speech through thematic studies of the Qur'an by applying the thematic interpretation method offered by Hasan Hanafi. The reading of the text according to Hanafi needs to go through three phases namely historical, eidetic and practical criticism. From this research, it was obtained that historically the Al-Qur'an was an authentic book since it was revealed until now, its truth was believed and used as a guide to Muslim life. Through eidetic criticism, the Qur'an reveals the prohibition of hate speech even condemns it. To overcome this, synergy efforts between the government, consumers and information producers must be done in combating hate speech by adapting values ​​in the Qur'an such as the tabayyun attitude for the community, the principles of honesty, accuracy, fairness, and others for information producers.